Endothelial inflammatory activation is related to myocardial perfusion disturbance in experimental chronic Chagas disease. (3rd October 2022) - Tanaka, D M; Fabricio, C G; Marin-Neto, J A; Barros-Filho, A C L; Lopes, C D; Oliveira, L F L; Mejia, J; Almeida, R R; Batah, S S; Nekolla, S G; Higuchi, M L; Cunha-Neto, E; et al.
Abstract: Background: Microvascular myocardial perfusion defect (MPD) is frequent in chronic Chagas cardiomyopathy (CCC) and may be involved in the pathophysiologic process that leads to left ventricular systolic dysfunction (LVSD). However, there is scarcity of studies addressing the histopathological meaning of MPD in CCC and its correlation with endothelial activation. Purpose: To investigate the correlations between MPD detected in vivo with functional and histopathological changes in the experimental model of CCC in hamsters. Methods: 24 female Sirius hamsters were investigated 8-months after intraperitoneal infection with 3.5x104 trypomastigote forms of Y-strain of T. cruzi. All animals were submitted to rest high-resolution 99mTc-Sestamibi-SPECT myocardial perfusion scintigraphy and echocardiography in vivo. The area of MPD was assessed through the calculation of polar maps by using a dedicated software (MunichHeart®) and a 13-segments model of LV. After euthanasia, we performed a histopathological study of cardiac inflammation and fibrosis and mRNA expression for TNF-α and ICAM, for assessment of inflammation and endothelial activation, respectively. Results: Most of the animals presented MPD, n=17 (71%), its extension ranging from 1.4 to 30.3% of LV surface. We observed lower values of LVEF in animals with MPD (38.5±11.2%) when compared with animals without MPD 48.4±9.1%, p=0.04) and a trend to higher intensity of myocardial inflammation (estimated by the number of mononuclear cells) in animals with MPD (540.4±153.6 cell/mm 2 ) vs. without MPD (409.6±130.3 cell/mm 2 ), p=0.09. In addition, animals with MPD presented a higher ICAM (0.02±0.01) expression when compared with animals without MPD (0.01±0.01, p=0.02). There was no difference between groups regarding the extent of fibrosis. The results of the regression and correlation analysis showed that individual values of MPD area presented negative correlation with LVEF (R=−0.6, p=0.001), with echocardiographic wall motion score index (WMSi, R=0.5, p=0.007), and with the number of mononuclear cells (R=0.5, p=0.01). Moreover, an analysis based on myocardial segments (n=312), showed that segments with MPD (n=54) in comparison to those without MPD (n=258) presented higher number of mononuclear cells (608±299.9 cell/mm 2 and 478.3±201.1 cell/mm, respectively, p<0.0001) and higher WMSi (1.8±0.9 and 1.2±0.4, respectively, p<0.0001. Conclusions: MPD is a common finding in experimental model of CCC in hamsters and is correlated with inflammation, endothelial inflammatory activation, and systolic ventricular dysfunction. These results suggest that perfusion defects may be an in vivo surrogate marker for inflammation with potential translational implication for monitoring disease activity. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Fundação de Amparo à Pesquisa do Estado de São Paulo